A magnetic nanowire platform for site specific treatment of testicular cancer - Nana, Abu Bakr Ahmed (My University, 2022)
Testicular Cancer (TC) incidence rates are projected to increase. Although contemporary treatment strategies have successfully cured patients with TC, they provide significant disadvantages which warrant the development of testicular saving treatments with decreased adverse effects. This aligns with the paradigm shift towards personalised medicine. The use of biomaterials science in nanomedicine with a focus on targeted delivery can advance the field with high impact. This research aimed to develop a magnetically targeted delivery platform composed of iron (Fe)/platinum (Pt) composite nanowires (NWs), combining the ferromagnetic behaviour of Fe with the cytotoxic activity of Pt against TC cells. In this regard magnetically active NWs for site specific treatment of TC were engineered using Pt as the model bioactive and characterized. NWs were chosen as the base archetype of this delivery platform due to the effect of the shape anisotropy of NWs on the magnetic properties of the delivery platform. Recent studies have shown that Pt is biocompatible, cytotoxic towards various cancerous cells, and has the potential to inhibit the growth of chemotherapy-resistant tumours. Pt was selected as the model bioactive due to its activity and the known susceptibility of TC to Pt based chemotherapy. Four types of NWs viz.; Fe-NWs, Pt-NWs, Fe-coated Pt-NWs, and dual Fe-Pt NWs were synthesised using template electro-deposition in which an anodic aluminium oxide (AAO) membrane was employed. The NWs were then characterised to analyse the physical, chemical, and structural properties using high-resolution transmission electron microscopy (HRTEM), powder X-ray diffraction (XRD), raman spectroscopy, vibrating-sample magnetometry VSM, inductively coupled plasma - optical emission spectrometry (ICP-OES), and zeta potential. The bioactivity of the synthesised NWs was determined by measuring the cell viability using the XTT assay to determine biocompatibility and cytotoxicity, and interaction between the synthesised NWs and cells was investigated using phase contrast imagery. The synthesised magnetic NWs had a high aspect ratio in terms of morphology with the desired lengths of <4µm and minimal diameter of 40-50 nm. All three Pt containing NWs displayed a polycrystalline structure as confirmed by powdered-XRD. Interestingly, single crystal Fe-NWs was confirmed by the single powdered-XRD peak at 2 θ 44.5° with Fe-NWs and Fe-coated Pt-NWs exhibited ferromagnetic behaviour which is conducive for magnetically targeted delivery. Fe-NWs displayed a large Ms of 2.2 Χ 106 A/m while Fe-coated Pt-NWs displayed a modest Ms of 21.6 Χ 103 A/m. The utility of the synthesised NWs was analysed for their potential use as a cytotoxic agent using TC cell line (Tera1) and mouse fibroblast (3T3). The single crystal Fe-NWs was found to be toxic to the non-cancerous 3T3 cells while the Pt-NWs, Fe-coated Pt-NWs and dual Fe-Pt NWs were found to be non-toxic to 3T3 cells but possessed dose-dependent toxicity to Tera-1 cells. The Fe/Pt composite NWs were more potent compared to pure Pt NWs. Pt-NWs had a high IC50 of 354 µg/mL while Fe-coated Pt-NWs and dual Fe-Pt NWs displayed an IC50 of 165 µg/mL and 207 µg/mL respectively. Fe-coated Pt-NWs displayed the most promising results in the development of a magnetically targeted delivery system aimed at treating TC. The cytotoxic activity of the platform can be enhanced with the addition of stimulus such as high and low frequency alternating magnetic fields to induce hyperthermia or mechanical cell death respectively or near IR radiation to induce hyperthermia. Thus, additional in-depth studies are warranted to assess a multimodal cell death application of the synthesised NWs in addition to extensive in vivo studies for the assessment of the preclinical efficacy for progression of this technology.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Pharmacy to the Faculty of Health Sciences, School of Therapeutic Sciences, University of the Witwatersrand, Johannesburg, 2022 .